A GIS-based Mapping of Mountain Peaks, Waterfalls and Mountain Lodges in North Macedonia - Jovanov, Stefan; Naumoski, Andreja (IEEE, 2020)
The World Health Organization recommends that we should walk at least 8000 steps per day, a great way to do that is to hike. Furthermore, we all know that hiking is always eco-friendly which means that hiking to the nearest waterfall or to the nearest mountain peak only grants us health and helps the environment. The Republic of North Macedonia as a country filled with mountains gives the people the perfect opportunity for hiking. By knowing how to choose the closest mountain lodge to our desired destination we are granted the most convenient way to an adventure. For this purpose in our paper we construct a map using ArcGIS software that contains mountain peaks and waterfalls in North Macedonia as well as the mountain lodges in their immediate vicinity. In addition, we conduct more detailed analysis and visualizations using Python and the libraries MatPlotLib, Numpy and Pandas. These analyses are conducted over the heights of the waterfalls and the elevation of the peaks as well as their distance to the mountain lodges. Hiking has always been and will always be a healthy habit that encourages eco-friendly tourism and grants extraordinary adventures.
Keywords: ArcGIS, Python, North Macedonia, Peaks, Waterfalls, Lodges, Hiking